Changes in Adults’ Eating Behaviors During the Initial Months of the COVID-19 Pandemic: A Narrative Review - Johnson, Ashlie N.; Clockston, Raeven Lynn M.; Fremling, Lindsey; Clark, Emma; Lundeberg, Pamela; Mueller, Megan; Graham, Dan J. (Journal of the Academy of Nutrition and Dietetics, 2023)
Factors such as regulations and health concerns shifted daily habits, including eating behaviors, during the early months of the coronavirus disease 2019 (COVID-19) pandemic. This comprehensive narrative review synthesizes research on eating behavior changes during the early months of the pandemic (February to June 2020), including changes in amount, rate, and timing of food consumption, types and healthfulness of foods consumed, the occurrence of other specified eating behaviors (eg, restrained eating or binging), and reasons for eating (eg, stress or cravings), among adults. A literature search using three EBSCOhost databases and Google Scholar was conducted to identify relevant articles made available in 2020. A total of 71 articles representing 250,715 individuals from more than 30 countries were reviewed. Findings show eating behaviors changed little during the early COVID-19 pandemic for most participants. Among those whose eating behaviors changed, increases in both intake and frequency of eating meals and snacks were more common than decreases. Findings on timing of eating and healthfulness of food consumed showed mixed results. However, when changes occurred in the type of food consumed, increases were more common for snacks, homemade pastries, white bread/pasta, legumes, and fruits/vegetables; decreases were more common for meats, seafood/fish, frozen foods, fast food, dark breads/grains, and dark leafy green vegetables. During the pandemic, binging, uncontrolled eating, and overeating increased, meal skipping decreased, and restrictive eating had mixed findings. Changes in factors such as emotions and mood (eg, depression), cravings, and environmental factors (eg, food insecurity) were related to changes in eating behaviors. Findings can inform clinical practitioners in efforts to mitigate disruptions to normal, healthy eating patterns among adults both in and outside of global health catastrophes.